Workplace Counterproductive Behavior: The Roles Of Locus Of Control, Organizational Constraints, And Organizational Justice - Deni Ramdani; Indah Ayu Johanda Putri; Mas Eko Affandi; Ivo Novitaningtyas; Sholeh Nur Rohmat (Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
In light of the fact that unproductive workplace behavior can have a significant negative effect on an organization, it is essential to do research on the factors that play a role in the emergence of unproductive workplace behavior in an organization. The work locus of control, organizational limits, and organizational equality have all been suggested as important factors in the development of counterproductive work behavior by a few previous studies and results based on observations made in the workplace. As a result, this line of research directs us to investigate the influence of those three characteristics on counterproductive behavior in the workplace. This goal will be accomplished by the use of multiple regression investigations, which will be used in the research. The results of a survey using a Likert scale have been analyzed here as part of this study. The key information was collected from 200 individuals who were representatives of the Directorate General of Taxation and came from a variety of work roles, locations, and organizational units. This was calculated by using a non probability sampling combined with the purposive technique. The findings of the hypotheses test have revealed that work locus of control, organizational limits, and organizational justice have a significant impact on counterproductive work behavior both partially and simultaneously. The measurement expressive also shows that the Directorate General of Taxes has a direct inner locus of control, lower organizational constraint discernment, and better organizational justice discernment. It is suggested that Directorate General of Taxes should further improve its internal control in order to complement the employees' self-discipline, maintain its organizational limitations, and ensure that organizational equality is maintained at an appropriate level.